2022
DOI: 10.1177/13506501221088525
|View full text |Cite
|
Sign up to set email alerts
|

Using DEM method to study graphite migration of copper-based graphite composites during friction

Abstract: The self-lubrication of copper-based graphite composites depends on the formation of a graphite lubricating film on the frictional interface, which results from the graphite migration from the matrix. In fact, the graphite migration process is difficult to observe and record during friction by experimental methods. In our work, a discrete element method (DEM) software “the Particle Flow Code in 2 Dimensions (PFC2D)” was employed to simulate and analyze the graphite migration dynamic process of copper-based gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The sample was observation by optical microscope after metallographic treatment. When near-surface composite material develop elastic-plastic deformation, the optical image of the near-surface composite will become blurred, the blurred size was determined by the ParCharm software, which was used to determine the critical migration depth, 25 Figure 8 shows migration depth at different test time.…”
Section: Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample was observation by optical microscope after metallographic treatment. When near-surface composite material develop elastic-plastic deformation, the optical image of the near-surface composite will become blurred, the blurred size was determined by the ParCharm software, which was used to determine the critical migration depth, 25 Figure 8 shows migration depth at different test time.…”
Section: Test Methodsmentioning
confidence: 99%
“…The lower sample was copper-based graphite composite, which was composed of copper particles with a diameter of 30 μm and 12vol% circular graphite clusters with a diameter of 30 μm, the graphite cluster was composed of several graphite particles with a radius of 3 μm. [24][25][26] The composite size was 2.5 × 1.2 mm. To make numerical model more close to the experimental situation, the powder metallurgical process of the lower sample was numerical simulated before friction.…”
Section: Numerical Model Of the Friction Pairmentioning
confidence: 99%
“…The graphite remains intact and only micro-cracks appear on the surface, which indicates that under a small load of 20N, the chips of the friction pair are not enough to pull out the graphite from the subsurface of the matrix to form a lubricating film. Chen et al [38] found that the migration of graphite was affected by the external load: the greater the external load, the greater the migration depth and the number of migration particles. Under the load of 50N, there are a lot of micro-scratches on the friction surface, but the depth and width are significantly reduced compared with those under the load of 20N, and there are also particles and debris on the friction surface.…”
Section: Friction Surface and Composition Analysismentioning
confidence: 99%
“…The common numerical simulation methods are finite element method (FEM) (Cotter, 2023;Yang et al, 2022), discrete element method (DEM) (Galashev and Abramova, 2023;Liang et al, 2023), molecular dynamics (MD) method (Cui et al, 2023;Kim et al, 2023), etc. Since the copper-based graphite composites prepared by powder metallurgy are composed of particle systems, the DEM is more suitable to simulate the composite friction process, and the DEM has been successfully used to simulate complex friction and wear processes (Xie et al, 2019;Chen et al, 2022). Xie et al (2019a) studied the dynamic evolution of the PTFE/45 steel friction pair friction interface, and analyzed the friction transfer of PTFE.…”
Section: Introductionmentioning
confidence: 99%